Evaluation of an Interactive Simulation of Continuity Related to the Operations and Recovery of Critical Infrastructure Facilities - Andrzej GRABOWSKI; Zuzanna URBAŃSKA; Dariusz KALWASIŃSKI (Problemy Mechatroniki)
Maintaining the continuous operation of Critical Infrastructure (CI) facilities and restoring them after a disaster is an important task for the functioning of individual communities and even the country as a whole. For this reason, tools are being developed to assist staff responsible for the operation of CI facilities. One interesting example of this type of tool is interactive training simulations implemented in virtual reality. This type of simulation allows procedures to be practised in situations where the continuity of the CI facility is threatened, and the procedures to be followed after a CI facility failure. This paper presents the possibilities of interacting with the virtual environment during a training simulation. Preliminary results are also discussed. Concerning research into the usability of such a training tool, the acceptance of the technology used etc.